2000
DOI: 10.1084/jem.191.3.435
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete Subpopulation of Dendritic Cells Transports Apoptotic Intestinal Epithelial Cells to T Cell Areas of Mesenteric Lymph Nodes

Abstract: This study identifies a dendritic cell (DC) subset that constitutively transports apoptotic intestinal epithelial cell remnants to T cell areas of mesenteric lymph nodes in vivo. Rat intestinal lymph contains two DC populations. Both populations have typical DC morphology, are major histocompatibility complex class IIhi, and express OX62, CD11c, and B7. CD4+/OX41+ DCs are strong antigen-presenting cells (APCs). CD4−/OX41− DCs are weak APCs and contain cytoplasmic apoptotic DNA, epithelial cell–restricted cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
602
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 833 publications
(634 citation statements)
references
References 46 publications
27
602
0
5
Order By: Relevance
“…This is also true for afferent lymph DC in other species [11][12][13]. Importantly, we have also shown that this phenotypic heterogeneity correlates with different functions in vivo, as iL-DC expressing low levels of CD172a selectively carry apoptotic material derived from intestinal epithelial cells to the T cell areas of the mesenteric lymph nodes (MLN) [2].…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…This is also true for afferent lymph DC in other species [11][12][13]. Importantly, we have also shown that this phenotypic heterogeneity correlates with different functions in vivo, as iL-DC expressing low levels of CD172a selectively carry apoptotic material derived from intestinal epithelial cells to the T cell areas of the mesenteric lymph nodes (MLN) [2].…”
Section: Introductionmentioning
confidence: 53%
“…The subset-specific lack of TLR7/8 expres-sion could be important for tolerance to self antigens, as the CD172a low iL-DC lacking TLR7 and 8 expression will be less likely to respond to their cargo of cellular debris, which includes ssRNA. That this could be important for self tolerance is supported by murine studies showing that CD8a + DC, which share the selective ability to take up dying cells in vivo [2,3], do not express TLR7, whereas CD8a -DC do [16].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Tolerance Introduction DC are professional antigen-presenting cells, which are well positioned in peripheral tissues to capture foreign antigens. DC are phagocytic and can ingest apoptotic cells, and hence are affected by the death of other cells in close proximity [1][2][3]. Clearance of apoptotic cells results in their removal from tissues, and provides protection from release of pro-inflammatory contents.…”
mentioning
confidence: 99%